(untitled) (Journal of history, 2022)
One of the traditional transports of the Kazakh people – the cart – is one of the most interesting and difficult topics. It can be used for lectures on ethnology, special courses, seminars, as well as for establishing interdisciplinary links in the field of ethnoarchaeology. The history of the formation of Kazakh household and household vehicles, their types and areas of distribution, methods of construction, features of their functions are considered. This issue has not been studied as a special topic in domestic and foreign ethnology. Archaeological excavations in the ancient settlements and mounds of the Kazakh land, which make up the base of objects, found things related to economic and household relations, which were considered from a scientific point of view to determine the genesis of transport. A written database on the ancient type of transports has been collected, analyzed and systematized, their level of study and historiography has been analyzed. An internal typology has been developed depending on the functional features of the carts. In addition to the specifics of the type and scope of application of the cart, regional, seasonal use, documents related to physical statistics were differentiated, their use in the economy, types of activities in the cart and databases of the cart in the historical era were revealed. An overview of the history of one of the household cars – a wagon was made. Analyzing physical and written databases, the carts were divided by typology as, early carts and medieval carts (houses on a cart, luxury carts).